SAVING BEHAVIOR: THE ROLE OF PRODUCT KNOWLEDGE AND INCOME WITH FINTECH AS A MEDIATION VARIABLE - Ade Gunawan (CERED Indonesia Institute, 2025)
A research approach is a design, guideline, or reference for the research to be conducted. This research approach is quantitative, in accordance with the problem being addressed in this study.Quantitative research methods are used to examine a specific population or sample using quantitative/statistical research instruments and data analysis to test hypotheses. This research focused on and was planned for Bank Syariah Indonesia (BSI) customers in Medan who actively use the BSI mobile banking application.A positive path coefficient indicates that Product Knowledge has a unidirectional relationship with Fintech usage, indicating that the influence of Product Knowledge on Saving Behavior is not significant. A positive path coefficient indicates that in terms of the direction of the relationship, an increase in income tends to be followed by an increase in saving behavior. A positive path coefficient indicates that in terms of the direction of the relationship, an increase in income tends to be followed by an increase in saving behavior